Joint ventures of foreign investment in dictatorial contexts: the case of the hotel industry in Cuba - Sebastián Rivero Silva (Atlantic Review of Economics (ARoEc), 2022)
This article studies the particularities of the creation and operation of foreign investment Joint Ventures in dictatorial regimes, with special emphasis on the relationship between dictatorship and investors. The hotel business in Cuba is studied in depth as a case study, since it is a paradigmatic example that shows the crossed interests in this type of operations. Thus, the dictatorial government seeks access to foreign currency to operate in the international market and exercise political control over the foreign business and its local workers. On the other hand, the foreign investor will want to develop his business without bureaucratic obstacles and to easily return the profits of the business to the parent company in the country of origin. Likewise, this article shows the legal structure of Joint Ventures from a technical point of view, bringing clarity to the creation and development of these operations, generally unknown due to their confidentiality and complexity.
Keywords: A12; B14; F50; 330; Foreign Investment; Dictatorship; Cuba; Joint Venture; Hotel Industry